Histopathological Features of Colorectal Polyps and Tumors at Sumber Waras Hospital from 2015-2023 - Jovial Jovial; Sony Sugiharto (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Colorectal tumours pose a significant global health issue, including in Indonesia. The development of colorectal polyps and tumours involves various risk factors such as poor lifestyle choices, male gender, and advancing age. This study aims to determine the characteristics of patients with colorectal polyps and tumours, their histopathological features, and the most common gender and age group for each histopathological feature. The study was conducted at Sumber Waras Hospital, implementing a descriptive cross-sectional approach with retrospective data of 113 patients with colorectal polyps and tumours from 2015-2023. This study's findings indicate that most patients were males (58.4%), with the highest number in the 61-70 age group (29.2%). Among non-neoplastic lesions, inflammatory polyp was the most prevalent histopathological finding (18.3%), whereas adenocarcinoma (NOS) was the most common feature among all neoplastic lesions (53.3%). All non-neoplastic lesions were predominantly found in males. Neoplastic lesions such as adenocarcinoma (NOS), mucinous adenocarcinoma, neuroendocrine tumours, and lymphoma were also more prevalent in males. In contrast, adenoma, signet ring, and squamous cell carcinoma were more frequently found in females. Non-neoplastic lesions such as hamartoma were most common in the 11-20 age group, while hyperplastic and inflammatory polyps were prevalent in the 61-70 age group. Neoplastic lesions such as adenoma were most prevalent in the 61-70 and 71-80 age groups; mucinous adenocarcinoma and lymphoma in the 51-60 age group; adenocarcinoma (NOS), squamous cell carcinoma, and neuroendocrine tumours in the 61-70 age group; as well as signet ring cell carcinoma in the 71-80 age group. To reduce the prevalence of colorectal polyps and tumours, it may be crucial to consider performing histopathological examinations for a thorough evaluation, given their wide variety that requires different diagnostic and treatment strategies. Keywords: Age Group, Colorectal Polyp, Colorectal Tumor, Gender, Histopathological Features